2013
DOI: 10.14742/ajet.95
|View full text |Cite
|
Sign up to set email alerts
|

Using a personal response system as an in-class assessment tool in the teaching of basic college chemistry

Abstract: <p>Since the introduction of personal response systems (PRS) (also referred to as "clickers") nearly a decade ago, their use has been extensively adopted on college campuses, and they are particularly popular with lecturers of large classes. Available evidence supports that PRS offers a promising avenue for future developments in pedagogy, although findings on the advantages of its effective use related to improving or enhancing student learning remain inconclusive. This study examines the degree to whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 26 publications
3
11
0
Order By: Relevance
“…In this regard, the usage of PRS in the course is a critical component in satisfying these requirements. In line with prior research, in this study, students found PRS to be simple and enjoyable to use, and they believed it improved their learning, class engagement, and overall classroom learning effectiveness (Chen & Lan, 2013). Consistent with previous studies, this study demonstrated that students found PRS to be enjoyable and straightforward to use and that it increased their learning, class engagement, and overall classroom learning effectiveness (Akkuş, Özkan & Çakır, 2021;Arthur & Owusu, 2020;Baltaci-Goktalay, 2016;Chen & Lan, 2013).…”
Section: Conclusion and Suggestionssupporting
confidence: 84%
“…In this regard, the usage of PRS in the course is a critical component in satisfying these requirements. In line with prior research, in this study, students found PRS to be simple and enjoyable to use, and they believed it improved their learning, class engagement, and overall classroom learning effectiveness (Chen & Lan, 2013). Consistent with previous studies, this study demonstrated that students found PRS to be enjoyable and straightforward to use and that it increased their learning, class engagement, and overall classroom learning effectiveness (Akkuş, Özkan & Çakır, 2021;Arthur & Owusu, 2020;Baltaci-Goktalay, 2016;Chen & Lan, 2013).…”
Section: Conclusion and Suggestionssupporting
confidence: 84%
“…98.5% of students reported that the system was easy to use and 92.5% perceived that the use of the system helped their learning (Lorimer and Hilliard, 2007). Other studies have reported similar findings (Jefferson and Spiegel, 2009;Chen and Lan, 2013). Despite many studies exploring the use of PRS for formative feedback, there is little information on the use on the use of PRS for summative assessment.…”
Section: Introductionmentioning
confidence: 63%
“…In relation to the items of the IRS-ITLP, they were written after an extensive bibliographic review on the three factors highlighted above ( 21 , 46 - 47 ) . Despite of the absence of experts on this field, this process provides validity to the questionnaire items.…”
Section: Methodsmentioning
confidence: 99%
“…Concerning the classroom environment factor, IRS increases attendance ( 21 ) and student participation ( 22 - 25 ) , resulting in a higher level of involvement during classes in comparison to the traditional methodology ( 23 , 26 - 27 ) . Within the learning factor, some studies establish that frequent and positive interaction makes classes more dynamic when using IRS ( 13 , 28 - 29 ) , promoting active learning ( 30 - 32 ) .…”
Section: Introductionmentioning
confidence: 99%